An investigation into the features of metaphor in "A farewell to arms" written by Ernest Hemingway and its Vietnamese version translated by Ha Giang VI (2005) - Nguyễn Thị Yến Ngọc (The University of Da Nang, 2014)
Introduction; Literature review and theoretical background; Methods and procedures; ...